2005
DOI: 10.1111/j.1439-0434.2005.00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Genetically Distinct Populations of Colletotrichum gloeosporioides Penz. Causing Anthracnose Disease of Yam (Dioscorea spp.)

Abstract: Variation within Colletotrichum gloeosporioides, the causal agent of yam anthracnose disease, is still poorly defined and this hinders breeding for resistance. Two morphotypes of C. gloeosporioides, designated slowgrowing grey (SGG) and fast-growing salmon (FGS), are associated with anthracnose disease of yam in Nigeria. The morphotypes are distinguishable based on colony and conidial morphology, growth rate, virulence, as well as vegetative compatibility, but molecular differentiation of SGG and FGS strains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 33 publications
(51 reference statements)
2
56
0
2
Order By: Relevance
“…Information on pathogen diversity and the geographic distribution of the pathogen population is therefore a prerequisite for accurate assessment of durable resistant germplasm in breeding programs (Abang, 2003). suggested that knowledge of pathotype diversity is important when choosing the appropriate isolates to screen for resistance in plant breeding programs.…”
Section: Pathogenic Variability Of Colleto-trichum Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on pathogen diversity and the geographic distribution of the pathogen population is therefore a prerequisite for accurate assessment of durable resistant germplasm in breeding programs (Abang, 2003). suggested that knowledge of pathotype diversity is important when choosing the appropriate isolates to screen for resistance in plant breeding programs.…”
Section: Pathogenic Variability Of Colleto-trichum Speciesmentioning
confidence: 99%
“…Abang (2003) stated that genetic population structure refers to the amount and distribution of genetic variation within and between populations. For example, how rapidly a pathogen can evolve could be indicated by the amount of genetic variation maintained within a population and then which may eventually be used to predict how long a control measure is probable to be effective (McDonald and Linde, 2002).…”
Section: Population Structure and Molecular Marker Techniquesmentioning
confidence: 99%
“…Yield losses of up to 90% have been reported under conditions favourable for disease development, while the disease is believed to be responsible for the disappearance of some popular cultivars of D. alata in the Caribbean (Winch et al 1984;McDonald et al 1998). Recent studies on C. gloeosporioides isolates associated with yam in the French West Indies (Frézal et al 2003;Frézal 2005) and in Nigeria (Abang et al 2004(Abang et al , 2005 revealed high genetic and pathogenic variations in between-field and withinfield isolates. Breeding for improved anthracnose resistance in farmers' preferred yam cultivars is the most reliable approach to disease management.…”
Section: Introductionmentioning
confidence: 97%
“…A combination of molecular diagnostic techniques and conventional morphological characterization is a suitable and reliable approach for studying Colletotrichum species/isolates complexes [80,81]. But it is very much difficult to diagnose the dormant infections of the C. falcatum fungus in seed canes under field conditions as red colour develops on stem and leaves at a later stage [82].…”
Section: Diagnostic Measuresmentioning
confidence: 99%